KAMPANYE PENINGKATAN PENGETAHUAN MAHASISWA UNIVERSITAS DIPONEGORO, UNIVERSITAS DIAN NUSWANTORO, DAN UNIVERSITAS KATOLIK SOEGIJAPRANATA TERHADAP BUS WISATA KOTA SEMARANG SEBAGAI ALTERNATIF STRESS RELIEF DALAM PERAN ACCOUNT EXECUTIVE, PRODUCER, ADMINISTRATION MANAGER, DAN PHOTOGRAPHER - Fadia Aulia Zuhri; Agus Naryoso (Interaksi Online, 2026)
The low level of student awareness regarding the Semarang City Tour Bus served as thebackground for implementing a communication campaign aimed at increasing understandingof the service as an alternative form of stress relief, as a preliminary survey of 115 studentsindicated that only approximately 20% were aware of its existence. This study analyzes theimplementation of a communication campaign that integrates Cyber Public Relations,Advertising, Event and Experience, and collaboration with Key Opinion Leaders (KOL),guided by the AISAS model (Attention, Interest, Search, Action, Share). In this project, theauthor served as Account Executive, Producer, Administration Manager, and Photographerduring the period of December 2025 to March 2026. The results show that the integratedcommunication strategy successfully increased students’ awareness and encouraged theirinterest in utilizing the Semarang City Tour Bus as a recreational activity and an alternativeform of stress relief.